THE EFFECT OF ELECTRONIC WORD-OF-MOUTH, PRODUCT FEATURES, AND LIFESTYLE ON BRANDSWITCHING AMONG MILLENNIAL CONSUMERS IN E-COMMERCE INDUSTRY - Nugroho, Dian Ari (Jurnal Aplikasi Manajemen, 2020)
The E-commerce industry was challenged with intense competition. Customers are easy to choose or switching any e-commerce websites for their reasons. This study aims to determine the effect of electronics word-of-mouth, product features, and lifestyle on brand-switching among millennial consumers in the e-commerce industry. It is explanatory research that was carried out at the millennial student of Universitas Brawijaya (University of Brawijaya), Indonesia. The data was collected using three methods: interview, questionnaire, and observation at the University of Brawijaya’s students. The object of this study was millennials customers, the user of e-commerce websites, especially college students. The sample was taken using non-probability sampling with a purposive sampling technique. Based on the results of the analysis and discussion, it can be concluded that electronic word-of-mouth, product features, and lifestyle influence consumers to switch from one e-commerce website to another.